2021
DOI: 10.1155/2021/5545007
|View full text |Cite
|
Sign up to set email alerts
|

Refractive Status in Eyes Implanted with Toric and Nontoric Intraocular Lenses during Combined Cataract Surgery and Microhook Ab Interno Trabeculotomy

Abstract: Purpose. To compare the refractive status between eyes implanted with toric and nontoric intraocular lenses (IOLs) during combined cataract surgery and microhook ab interno trabeculotomy (μLOT), a minimally invasive glaucoma surgery (MIGS). Methods. Twenty eyes of 20 patients who had open-angle glaucoma, cataract, and preexisting regular corneal astigmatism exceeding 1.5 diopters (D) and underwent combined μLOT and phacoemulsification were recruited retrospectively. Ten eyes were implanted with a toric IOL and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Full-text assessment was performed on the remaining 13 records; 2 were not retrieved, and 1 additional study was included from citation searching ( Figure 1 ). Twelve studies [ 22 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ] fulfilled the inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Full-text assessment was performed on the remaining 13 records; 2 were not retrieved, and 1 additional study was included from citation searching ( Figure 1 ). Twelve studies [ 22 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ] fulfilled the inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies [42,[44][45][46][47] reported astigmatism outcomes. Ichioka et al 2021) [46] included 20 POAG eyes (20 patients) with pre-existing corneal astigmatism exceeding −1.5 D implanted with either non-toric (n = 10) or toric IOLs (n = 10).…”
Section: Astigmatismmentioning
confidence: 99%
“…[16] Previously, reasons for SIA after LEC were reported to be a gap around the scleral flap [1], sinking of the limbus because of the tissue loss under the scleral flap [17], tissue contraction due to extensive scleral cautery [18], subconjunctival scarring [19,20], corneal steepening due to the compression of a bleb by eyelid [18], and postoperative hypotony. [4] Absence of these possible mechanisms explains the small SIA by iStent [9] and other goniotomy-related MIGSs procedures [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…The study design and methods for statistical analyses were followed our previous works that tested the the roles of toric IOLs during TMH [ 7 , 8 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation